'La Nouvelle Activité des Trafiquants de Femmes': France, Le Havre and the Politics of Trafficking, 1919–1939. (5th December 2016) - MARSH, KATE
Abstract : This article examines how the 'moral panic' about sex trafficking during the interwar years manifested itself in Le Havre, a French port which, at the beginning of the twentieth century, had become synonymous with the illegal trade. Interrogating hitherto neglected material in departmental archives, it explores how the problem of the trafficking of women ( la traite des femmes ) changed after 1919, how the administrative consequences of directives by the League of Nations could influence behaviours in everyday life and how an episode of female migration from Eastern Europe interacted with French political agendas to magnify and, in some cases, generate a problem.